2019
DOI: 10.1038/s41467-019-10340-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electrons transform the nimorazole molecule into a radiosensitiser

Abstract: While matter is irradiated with highly-energetic particles, it may become chemically modified. Thereby, the reactions of free low-energy electrons (LEEs) formed as secondary particles play an important role. It is unknown to what degree and by which mechanism LEEs contribute to the action of electron-affinic radiosensitisers applied in radiotherapy of hypoxic tumours. Here we show that LEEs effectively cause the reduction of the radiosensitiser nimorazole via associative electron attachment with the cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 51 publications
(111 citation statements)
references
References 43 publications
(50 reference statements)
5
105
0
1
Order By: Relevance
“…The anion efficiency curves for mass-selected fragment anions were obtained with a high-resolution crossed electron–molecular beam apparatus, which consists of a hemispherical electron monochromator (HEM) combined with a quadrupole mass analyzer. The experiment is described in detail in ref ( 33 ). The sample molecules were placed in a copper oven installed in a vacuum chamber.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…The anion efficiency curves for mass-selected fragment anions were obtained with a high-resolution crossed electron–molecular beam apparatus, which consists of a hemispherical electron monochromator (HEM) combined with a quadrupole mass analyzer. The experiment is described in detail in ref ( 33 ). The sample molecules were placed in a copper oven installed in a vacuum chamber.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…The electronic structure of nimorazole [7] and the formation of negative ions via dissociative electron attachment (DEA) processes were also investigated using different spectroscopic techniques. The recent work of Meißner et al [8] has demonstrated that low-energy electrons are responsible for reduction of nimorazole via associative electron attachment, which corroborates the rationale that the radiosensitization process of this molecule in tumour cells is a result of reduction inside the cells. In contrast, Meißner and co-workers [9] have also investigated the role of low-energy electrons in misonidazole, showing that this molecule does not undergo reduction but rather dissociates in several anionic species leading to formation of radicals which are highly reactive to the hypoxic cell.…”
Section: Introductionmentioning
confidence: 63%
“…These results reinforce the effect that a third body (K + ) in the collisional system may stabilize the parent anion of these molecules. These results strongly suggest that radical anion formation seems to be the initial step for the impact of nitroimidazoles as radiosensitisers in hypoxic tumour cells [8] The NO 2 − yield is, together with the parent anion, one of the most intense in the nitroimidazoles TOF mass spectra, which is unsurprising because of NO 2 electron affinity, 2.27 eV [28]. For lower collision energies (e.g., 30 eV in the lab frame, Figure 2) and in the case of the methylated compounds, NO 2 − corresponds to the most intense anion.…”
Section: Parent Anion Formationmentioning
confidence: 75%
See 1 more Smart Citation
“…Die Bildung freier Radikale kann durch die Anlagerung von NEEs effizient ausgelçst werden, wie in früheren Untersuchungen mit potenziellen Krebsmedikamenten wie Nimorazol und modifizierten Pyrimidinen gezeigt wurde. [7,8] Die jüngsten Studien mit Nimorazol [9] stützten die Hypothese, dass der Mechanismus der Radiosensibilisierung durch diese Verbindung auf der anfänglichen Bildung des intakten Radikalanions beruht, das im weiteren Verlauf DNA-Schäden verursacht.…”
unclassified